(3GdQHG hGdaGFOI GdeUQajI (B:s (3OQGSI ebGQfI (B/s - (3YjO, YGOd YHO GdaVjd,s 1969- ((3GdEScfOQjI, eUQ (B:s (3OGQ GdJYdje GdLGeYj,s, 2023)
(3jMJhj gPG GdcJGH Ydi SJ aUhd MjK jJfGhd GdaUd GdChd (B"(3JYQja GdQHG hGdaGFOI GdeUQajI(B" (3hjJfGhd GdaUd GdKGfj (B"(3SYQ GdaGFOI heDTQ GdQHM(B"(3, hjJfGhd GdaUd GdKGdK (B"(3GdJehjd HGdaGFOI GdeUQajI(B"(3, hGdaUd GdQGHY jJfGhd ajg (B"(3UhQ GdQHG hGdaGFOI aj GdeYGedGJ GdQHhjI(B" (3hjTed GdaUd GdNGeS (B"(3bQGQGJ GdQHG hGdaGFOI(B" (3hjJfGhd GdaUd GdSGOS hGdCNjQ GSJKeGQ GdCehGd aj GdHfhc GdJj JMOO GdQHM ebOeG(B".s
(3HHdjhLQGajI (B: (3UaMI (B321-325.s
Keywords: (3GdQHG (B((3abg ESdGej(B)s; (3GdbQhV (B((3abg ESdGej(B)s; (3GdaGFOI (B((3abg ESdGej(B)s